Studi Kondisi Operasi dalam Pemisahan Asam Laktat dari Produk Konversi Katalitik Tandan Kosong Sawit Melalui Esterifikasi-Hidrolisis - Johnner Parningotan Sitompul; Ana Kemala Putri Jauhari; Gun Gun Gumilar; Yosandi Calimanto; Carolus Borromeus Rasrendra (Jurnal Rekayasa Proses, 2019)
Lactic acid is a platform chemical that is usually used to form various chemical products. Nowadays, the need of lactic acid is increasingly high especially for bio-based chemical as a substitute for petroleum-based one. Catalytic chemical conversion is seemingly potential to substitute the bioconversion pathway. This research aims to determine the best operating condition for separating lactic acid from its mixture (the catalytic conversion product of oil palm empty fruit bunch) by esterification-hydrolysis in order to produce the highest yield and purity. The esterification of the mixture was carried out by using n-butanol as a solvent and wet Amberlyst-15 as a catalyst. The esterification process was conducted by reacting n-butanol and lactic acid for 6 hours in a batch reactor. Hydrolysis was then followed by reacting organic phase as an esterification product and water in batch reactor system for 4 hours. The result showed that the higher reactant volume ratio, temperature, and catalyst concentration were used, the higher yield of both esterification and hydrolysis products would be. The highest esterification yield of 98.64%-w/w was achieved when the temperature was at 90oC, with a reactant volume ratio of 4, and the catalyst concentration of 2.5%-w/w. Moreover, the experiment results showed that the highest hydrolysis yield of 98.64%-w/w was achieved by the temperature of 90 oC, the reactant volume ratio of 20, and the catalyst concentration of 2.5%-w/w. It was revealed that the most significant variable for esterification was reactant volume ratio while both reactant volume ratio and temperature become the prominent variables for hydrolysis counterpart. Additionally, another modified method of separation was conducted by applying reactive distillation. This modified process increased the hydrolysis yield up to 82.34%-w/w by using pure butyl lactate as feed while the usage of the catalytic butyl lactate as feed could produce lactic acid with the yield of 74.01%-w/w. A B S T R A KAsam laktat adalah bahan kimia antara yang bermanfaat untuk pembentukan berbagai macam produk kimia. Permintaan asam laktat dewasa ini sangat tinggi terutama sebagai bahan kimia berbasis alam yang digunakan sebagai substitusi untuk penggunaan bahan kimia tak terbarukan. Terdapat banyak alternatif proses yang sudah dilakukan oleh peneliti untuk menemukan metode alternatif yang efektif sebagai pengganti proses fermentasi dan konversi katalitik merupakan proses yang berpotensi untuk diaplikasikan. Penelitian ini bertujuan untuk menentukan kondisi operasi yang menghasilkan perolehan asam laktat tinggi pada reaksi esterifikasi-hidrolisis asam laktat dari produk reaksi katalitik tandan kosong sawit menggunakan n-butanol p.a., dan katalis Amberlyst-15 basah. Esterifikasi dilakukan dengan mereaksikan n-butanol dan umpan hasil konversi katalitik tandan kosong sawit selama 6 jam. Hidrolisis dilakukan dengan mereaksikan air dan fase organik esterifikasi selama 4 jam. Hasil menunjukkan semakin tinggi temperatur reaksi, rasio volume reaktan, dan konsentrasi katalis, semakin tinggi perolehan asam laktat esterifikasi dan hidrolisis yang dihasilkan. Perolehan butil laktat tertinggi pada reaksi esterifikasi diperoleh sebesar 98,64%-b/b pada kondisi 90 oC, rasio volume 4 dan konsentrasi katalis 2,5%-b/b. Perolehan asam laktat tertinggi pada reaksi hidrolisis diperoleh sebesar 67,97%-b/b pada kondisi 90 oC, rasio volume 20 dan konsentrasi katalis 2,5%-b/b. Variabel signifikan pada esterifikasi adalah rasio volume reaktan, sedangkan pada hidrolisis adalah rasio volume reaktan dan temperatur. Penggunaan distilasi reaktif pada hidrolisis mampu meningkatkan perolehan asam laktat hingga 82,34%-b/b untuk butil laktat murni sebagai umpan dan 74,01%-b/b untuk butil laktat katalitik sebagai umpan.